2020
DOI: 10.1101/2020.04.09.20059758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Scalable Method of Applying Heat and Humidity for Decontamination of N95 Respirators During the COVID-19 Crisis

Abstract: A lack of N95 respirators during the COVID-19 crisis has placed healthcare workers at risk. It is important for any N95 reuse strategy to determine the effects that proposed protocols would have on the physical functioning of the mask, as well as the practical aspects of implementation. Here we propose and implement a method of heating N95 respirators with moisture (85 o C, 60-85% humidity). We test both mask filtration efficiency and fit to validate this process. Our tests focus on the 3M 1860 and 3M 8210 Plu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 16 publications
1
26
0
1
Order By: Relevance
“…In contrast, a number of studies have shown that both dry and moist heat treatment of FFRs in the range of 70–85 °C were possible for extended periods of time ( Table 8 ), without marked effects on respirator performance and/or fit ( Table 7 ). These have ranged from 90 to 600 min (cumulative) at 70 °C using dry or moist heat [ 39 , 68 , 93 , 96 , 97 ], to 150–400 min (cumulative) at 85 °C with low-moisture (30% RH) to 100% RH [ 44 , 92 ] ( Table 8 ). Liao et al [ 44 ] also reported that the particle filtration efficiency of the meltblown fabric of N95 FFRs was not markedly affected after 1500 min of dry heat treatment at 75 °C or after 1000 min at 85 °C and 30% RH ( Table 7 and Table 8 ).…”
Section: Impact Of Disinfection On Ffrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a number of studies have shown that both dry and moist heat treatment of FFRs in the range of 70–85 °C were possible for extended periods of time ( Table 8 ), without marked effects on respirator performance and/or fit ( Table 7 ). These have ranged from 90 to 600 min (cumulative) at 70 °C using dry or moist heat [ 39 , 68 , 93 , 96 , 97 ], to 150–400 min (cumulative) at 85 °C with low-moisture (30% RH) to 100% RH [ 44 , 92 ] ( Table 8 ). Liao et al [ 44 ] also reported that the particle filtration efficiency of the meltblown fabric of N95 FFRs was not markedly affected after 1500 min of dry heat treatment at 75 °C or after 1000 min at 85 °C and 30% RH ( Table 7 and Table 8 ).…”
Section: Impact Of Disinfection On Ffrsmentioning
confidence: 99%
“…Of note, even at the lower end of the temperature range (60 °C), three studies from the same group using moist heat incubation (80% RH) [ 78 , 79 , 80 ] reported that while cumulative treatment times of 30–90 min did not significantly affect FFR performance and fit, there was separation of the inner foam nose cushion for a given respirator model ( Table 7 ). In addition, as reported for UGVI treatment, some FFRs failed fit or particle filtration testing even before treatment [ 92 , 95 , 97 ], and the ability of different models to withstand high-temperature insults varied [ 88 ]. Further, while a number of studies have shown that many FFR models can withstand multiple disinfection cycles with heat at 70 to 85 °C ( Table 8 ), the findings reported by Fisher et al suggest that this may not be necessarily applicable in practice, when treatment cycles are interpolated with periods of actual FFR wear [ 39 ] ( Table 7 ).…”
Section: Impact Of Disinfection On Ffrsmentioning
confidence: 99%
“…The possibility that disposable N95 masks could be sterilized and reused was raised 15 years ago as a strategy to address shortages arising from medical emergencies, [3][4][5] but with the exception of a single FDA-funded study by the Battelle Memorial Institute, 6 little subsequent research was performed on the topic. Recently, in response to acute N95 mask shortages, multiple strategies for mask sterilization have been proposed and studied, including exposure to ultraviolet (UV) germicidal irradiation, vaporized hydrogen peroxide, moist heat, ethylene oxide, and gamma irradiation [7][8][9][10][11][12][13][14] . In this study, we evaluate a recently developed technology, ionized hydrogen peroxide (iHP), as a method for sterilizing N95 masks and other PPE.…”
Section: Introductionmentioning
confidence: 99%
“…11 Several strategies have been proposed for conserving PPE including repurposing other devices to be used as FFRs, creating FFRs at home and decontamination of N95s using methods such as ultraviolet-C germicidal irradiation, dry heat, moist heat, and vaporized hydrogen peroxide. [12][13][14][15] Vaporized hydrogen peroxide (VHP) was given provisional US Food and Drug Administration (FDA) Emergency Use Authorization (EUA) for decontamination of used N95 respirators. 16 However, VHP decontamination is a labor and timeintensive process due to a long treatment cycle and requires the shipment of used N95 respirators to a central processing center.…”
Section: Introductionmentioning
confidence: 99%